ANALISIS MINAT MENABUNG MASYARAKAT PADA BANK MUAMALAT DI KOTA KISARAN - Dita Pertiwi; Haroni Doli Ritonga (Ekonomi dan Keuangan, 2012)
The purpose of this research is to know how far service in medium and transaction. As well as the factor of trust and location that influence the people to save their money in Bank Muamalat Kisaran. The second purpose is to know what factor is dominant to push the people to become customers. The data used is primary data and secondary data. The primary data is collected from the chosen respondent in Kisaran who save their money at Bank Muamalat in Kisaran. The questionnaire is answered by 100 respondents that chosen randomly. The secondary one are obtained from Bank Muamalat Indonesia documents, website and other media. The analysis method is descriptive supported using grafic, crossing tabulation, table and frequency.The result indicates customers decide to save because of trust factors relatively dominant in Bank Muamalat Indonesia Kisaran.